2007
DOI: 10.1002/pip.795
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution morphological and electrical characterisation of organic bulk heterojunction solar cells by scanning probe microscopy

Abstract: State-of-the-art organic bulk heterojunction (BH) solar cells, also called excitonic solar cells, are based on intimate mixtures of donor and acceptor organic materials of which the nanoscale morphology strongly influences both the photovoltaic performances and the stability of the device. In particular, the form and the size of the three-dimensional (3D) interpenetrating network of donor/acceptor material is shown to be crucial for the electrical transport properties and the resulting photovoltaic properties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 70 publications
0
32
0
Order By: Relevance
“…[11] The later observation lead to the picture that PSS is transported towards the surface upon applying the high tip sample voltage. Douheret and co-workers reported that the topography of poly(3-hexylthiophene) and [6,6]-phenyl C61-butyric acid methyl ester (P3HT:PCBM) was slightly altered upon scanning in contact mode using cantilevers with a spring constant <1 N Á m. [12] However, at a bias potential of À1 V, currents of 10 pA lead to significant degradation of the electrical properties of the scanned area. The internal structure of bulk heterojuntion P3HT:PCBM films of the surface and focused ion beam cross-sections were investigated.…”
Section: Scanning Conductive Force Microscopy (Scfm)mentioning
confidence: 99%
“…[11] The later observation lead to the picture that PSS is transported towards the surface upon applying the high tip sample voltage. Douheret and co-workers reported that the topography of poly(3-hexylthiophene) and [6,6]-phenyl C61-butyric acid methyl ester (P3HT:PCBM) was slightly altered upon scanning in contact mode using cantilevers with a spring constant <1 N Á m. [12] However, at a bias potential of À1 V, currents of 10 pA lead to significant degradation of the electrical properties of the scanned area. The internal structure of bulk heterojuntion P3HT:PCBM films of the surface and focused ion beam cross-sections were investigated.…”
Section: Scanning Conductive Force Microscopy (Scfm)mentioning
confidence: 99%
“…As was the case with KFM and EFM, there have been a few CS-AFM studies of the polymer blends [67][68][69][70][71] generally showing inhomogeneity due to pronounced phase segregation in these systems. Further details can be found in a recent review [52].…”
Section: Current-sensing Atomic Force Microscopy (Cs-afm)mentioning
confidence: 99%
“…Due to the importance of morphology for the function of organic solar cells much effort have been put into examining the phase structure. Commonly this is done with techniques such as atomic force microscopy (AFM) (Roman et al , 1997; Douheret et al , 2007; Dante et al , 2008), including Kelvin probe force microscopy and conductive AFM (Douheret et al , 2007), or scanning electron microscopy (SEM) (Hoppe et al , 2004). These techniques are used to map the surface topography and material differences, as well as electrical properties.…”
Section: Introductionmentioning
confidence: 99%